Geriatric assessment of older patients receiving Trabectedin in first-line treatment for advanced soft tissue Sarcomas: the E-TRAB study from the German Interdisciplinary Sarcoma Group (GISG-13) - Kasper, Bernd; Pink, Daniel; Rothermundt, Christian; Richter, Stephan; Augustin, Marinela; Kollar, Attila; Kunitz, Annegret; Eisterer, Wolfgang; Gaidzik, Verena; Brodowicz, Thomas; Egerer, Gerlinde; Reichardt, Peter; et al. (Cancers, 2024)
E-TRAB was a non-interventional, prospective trial investigating the feasibility and predictive value of geriatric assessments (GA) in older STS patients treated with trabectedin as first-line therapy. Primary endpoints were overall survival (OS), quality of life and individual clinical benefit assessed by the patient-reported outcome measures QLQ-C30 and PRO-CTCAE. Further, several GA tools were applied and correlated with clinical outcomes and treatment-related toxicities. The final analyses included 69 patients from 12 German-speaking sites. The median age of patients was 78 years (range: 55 to 88). Baseline data on PROs and GA identified a diverse population of older patients with respect to their global health status, although a large proportion of them suffered from limitations, required geriatric help and had a high risk of morbidity. The Cancer and Age Research Group (CARG) score classified 38%, 29% and 23% of the patients with low, intermediate and high risks for therapy-related side effects, respectively. Median OS was 11.2 months [95%CI: 5.6; 19.4]. The study confirmed that trabectedin as first-line treatment in older patients with STS has an acceptable and manageable safety profile. Potential prognostic factors for clinical outcome and therapy-related toxicity were identified among the GA tools. Long Timed Up and Go (TUG) showed a significant correlation to OS and early death, whereas a high CARG score (>9) was associated with an increase in unplanned hospitalizations and the incidence of toxicities grade ≥ 3.
Gesehen am 25.06.2024